Qualidade de vida relacionada à voz de professores: uma revisão sistemática exploratória da literatura - Ribas, Tânia Maestrelli; Penteado, Regina Zanella; García-zapata, Marco Tulio A. (CEFAC - Saúde e Educação, 2014)
The objective of this study was to verify, through a systematic revision of literature, the existents studies on quality of life concerning to the voice of professors. It was accepted articles of the Education Resources Information Center (ERIC,)LILACS, PUBMED Central(PMC) and SCIELO in Portuguese, English or Spanish, using the uniterms “quality of life’ and ‘voice’, without determination about the period of publication. The articles had been enclosed in accordance with standardized formularies. The initial search resulted in 315 articles. For articles selection were previously established inclusion and exclusion criteria applied and the Relevance Tests I and II. Articles were included according to standardized forms. The initial search resulted in 315 articles. The analysis process involved reading of headings, abstracts and complete texts; and only 13 articles had filled the inclusion criterion, involving studies of quality of life concerning to the voice of professors of the diverse levels of education (infantile, basic, average and superior) of public and private schools. The quality of life in voice was the most widely used instrument with teachers, and the physical domain of instrument was the one which impacted in a negative way in the quality of life concerning to the voice, considering speaking loud in noisy environments and the air finishes fast and needs to breathe many times while speaks. It had certain difficulty at the moment of the analyses of the articles, since that it had not presented similar standardization of techniques and criterion. There is the necessity of increasing the studies of quality of life concerning to the voice of the professor in the different levels of education and types of schools.

O objetivo deste estudo foi verificar, por meio de uma revisão sistemática de literatura, os estudos existentes sobre qualidade de vida relacionada à voz de professores. Foram selecionados artigos, nas seguintes bases de dados: Education Resources Information Center (ERIC,) LILACS, PUBMED Central(PMC) eSCIELO.Foram empregados os unitermos ‘qualidade de vida’ e ‘voz’ e seus correspondentes na língua inglesa. Foram aceitos artigos em inglês, português ou espanhol, sem determinação quanto ao período de publicação. Para a seleção dos artigos foram previamente estabelecidos critérios de inclusão e exclusão e aplicados os Testes de Relevância I e II. Os artigos foram incluídos de acordo com formulários padronizados. A busca inicial resultou em 315 artigos. O processo de análise envolveu leitura de títulos, resumos e textos completos; sendo que apenas 13 artigos preencheram os critérios de inclusão, envolvendo estudos de qualidade de vida relacionada à voz de professores dos diversos níveis de ensino (infantil, fundamental, médio e superior) e de escolas públicas e privadas. O QVV foi o instrumento mais utilizado com professores; sendo o domínio físico deste instrumento o que impactou de forma mais negativa na qualidade de vida relacionada à voz no que se refere a falar forte em ambientes ruidosos e o ar acabar rápido e precisar respirar muitas vezes enquanto fala. Houve certa dificuldade no momento das análises dos artigos, uma vez que não apresentaram padronização de técnicas e critérios semelhantes. Há necessidade de aumento dos estudos de qualidade de vida relacionada à voz do professor nos diferentes níveis de ensino e tipos de escolas.
Quality of life related with the voice of teachers: exploratory systematic review of literature
Keywords: Quality of Life; Voice; Faculty; Speech, Language and Hearing Sciences; Public Health; Qualidade de Vida; Voz; Docente; Fonoaudiologia; Saúde Pública